Development of ointments based on Solanum nigrum and Baccharis latifolia for muscle relaxation in athletes. - Benavides Montenegro, John Sebastián
The development of therapeutic products for healing preparations has turned its attention to the use of compounds present in plants, therefore, this  research focused on developing and evaluatingthe healing power of an ointment from Blackberry plants (Solanum nigrum) and Chilca Negra (Baccharislatifolia) grown in the Gran Cumbal region (Nariño, Colombia) and at the same time combined withrelaxation techniques to improve muscle recovery in athletes. Leaves of both species were used to obtainthe extracts by means of the extraction method with ethanol (70% V / V). The extract obtained was used for the preparation of the ointment and its application by means of a shaking, pinching and twisting massage technique to four groups of eight people. As a result, it was observed that the best mechanism to enhance the effect of the compounds present in plants was the combination of the three muscle relaxation techniques, the validation of healing power was obtained through an acceptance survey; reporting that more than 57% of the people perceived a sensation of improvement after the application and the massage.